2023
DOI: 10.3390/md21020117
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Investigation of Three Cystoseira Species and Their Larvicidal Activity Supported with In Silico Studies

Abstract: Culex pipiens mosquitoes are transmitters of many viruses and are associated with the transmission of many diseases, such as filariasis and avian malaria, that have a high rate of mortality. The current study draws attention to the larvicidal efficacy of three methanolic algal extracts, Cystoseira myrica, C. trinodis, and C. tamariscifolia, against the third larval instar of Cx. pipiens. The UPLC-ESI-MS analysis of three methanol fractions of algal samples led to the tentative characterization of twelve compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 74 publications
1
7
0
Order By: Relevance
“…Alghazwi et al [ 12 ] summarized the macroalgae-derived compounds that are targeting cholinesterase activity and, in our research, loliolide and fucoxanthin have been found in both tested samples, while α-linolenic acid was found only in D. dichotoma sample, as molecules with enzyme inhibitory effects [ 10 , 94 ]. Aly et al [ 95 ] reported the presence of α-linolenic acid and cystoseirol monoacetate, compounds with good binding affinities to the AChE enzyme [ 95 ], in the methanolic fraction of several Cystoseira species, while the same compounds were also determined in this research for the D. dichotoma F3 fraction. On the other hand, ethanolic extracts of D. dichotoma did not show inhibitory effects on acetylcholine esterase [ 94 ].…”
Section: Discussionsupporting
confidence: 62%
“…Alghazwi et al [ 12 ] summarized the macroalgae-derived compounds that are targeting cholinesterase activity and, in our research, loliolide and fucoxanthin have been found in both tested samples, while α-linolenic acid was found only in D. dichotoma sample, as molecules with enzyme inhibitory effects [ 10 , 94 ]. Aly et al [ 95 ] reported the presence of α-linolenic acid and cystoseirol monoacetate, compounds with good binding affinities to the AChE enzyme [ 95 ], in the methanolic fraction of several Cystoseira species, while the same compounds were also determined in this research for the D. dichotoma F3 fraction. On the other hand, ethanolic extracts of D. dichotoma did not show inhibitory effects on acetylcholine esterase [ 94 ].…”
Section: Discussionsupporting
confidence: 62%
“…The findings of Sayed et al (2020) suggest that Ochradenus baccatus can be used as an effective insecticide in IPM programs against Aphis craccivora. Plant extracts and EOs are new technology in insecticide formulations that can be utilized in pest control (Moustafa et al 2021;Awad et al 2022;Aly 2023). Our results show that the toxicity indices of clove and basil Eos were 100 and 22.45%, respectively.…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, Bedia et al (2019) emphasized the photocatalytic performance of MOFs in the purification of water and discussed the degradation of organic pollutants, such as dyes and pharmaceuticals, as well as the removal of heavy metal ions using MOF-based photocatalysts. MOFs with a very large surface area, tunable porosity, tailorable topology, crystallinity, adjustable functionalities, excellent photoelectronic properties and high thermal and mechanical stability could eradicate prevailing challenges to help water treatment The expansion of highly invasive species such as mosquitoes has led to the emergence of deadly diseases that can lead to epidemics or pandemics (Dahmana & Mediannikov, 2020; Aly et al, 2023). The larvicide bioassay was conducted using different concentrations of Fe-MOF nanoparticles dissolved in distilled water.…”
Section: Discussionmentioning
confidence: 99%